PENGARUH PENGGUNAAN PLICKERS TERHADAP HASIL BELAJAR DAN PERSEPSI SISWA DALAM PEMBELAJARAN MATEMATIKA DI KELAS VI SDN KARAH 1 SURABAYA - Alda Maysita Budianto; Farida Istianah; Mintartik; Choirun Nisa; Herlina Desemi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Learning mathematic is often faced with low student participation and unsatisfactory learning outcomes, especially when the teaching methods used are not interactive. One innovative solution to address this issue is by utilizing educational technology, such as the Plickers application, which allows real time interaction and provides immediate feedback to students. This study aims to evaluate the impact of using Plickers on learning outcomes and student perceptions in mathematics learning in grade VI at SDN Karah 1 Surabaya. Using the Classroom Action Research (CAR) method with one cycle, this study involved a pretest, the implementation of Plickers, a posttest, and student interviews. The results showed a significant increase in the students' average scores, from 48.46 in the pretest to 85.38 in the posttest. Interviews also revealed that students felt more engaged and interested during lessons using Plickers, despite some technical difficulties. This study concludes that Plickers is effective in improving learning outcomes and student participation in mathematics learning.